Using Satellite Imagery to Revolutionize the Creation of Tax Maps - Ali, Daniel Ayalew (World Bank, Washington, DC, 2018)
Globally, cities rely on property taxes as a key source of revenues to finance the services that enhance its long-term competitiveness and counter the negative aspects of density. In developing countries, the technical complexity of ensuring that tax rolls are complete and valuations current is often perceived as a major barrier to bringing in more property tax revenues. This policy paper shows how high-resolution satellite imagery makes it possible to assess the completeness of existing tax maps by estimating built-up areas based on building heights and footprints. Together with information on sales prices from the land registry, targeted surveys, and routine statistical data, this makes it possible to use mass valuation procedures to generate tax maps. The example of Kigali illustrates the reliability of the method and the potentially far-reaching revenue impacts. Estimates based on modelling show that heightened tax compliance and a move to a one percent ad valorem tax would yield a tenfold increase in revenue from public land.